Development of Microstrip Monopole Antenna Integrated with Light Emitting Diode (LED) - Kamarudin, S.N.; Ali, M.T.; Subahir, S.; Yon, H. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents the integration of Microstrip Antenna with Light Emitting Diode (LED). The objective of this design is to have a dual application in one single antenna, which is for wireless communication and illumination. Based on the result, the frequency is inversely proportional to the increase of the antenna size. The LED itself acts as a conductance for the antenna as it is also a part of the antenna. The antenna design is based on the structure of monopole antenna at 3.6 GHz. To design the antenna structure, Computer Simulation Technology (CST) was used with the permittivity, r = 4.3 thickness, h = 1.6mm on FR4 substrate. The SMD5050 LED was used to integrate the antenna structure in parallel connection. The effects of integrating the LED into the antenna structure of antenna were determined through the performance of antenna in terms of return loss, gain, directivity and the efficiency. The results are 3.88GHz during the OFF state for the resonant frequency with -23.88dB return loss, whereby the results during the ON state are 3.75 GHz and -21.2 dB, respectively.